2021
DOI: 10.3390/jcm10081675
|View full text |Cite
|
Sign up to set email alerts
|

Management of Implantable Cardioverter-Defibrillators during Pregnancy—A Systematic Review

Abstract: Background: With the advent of implantable cardioverter-defibrillator (ICD) technology in recent decades, patients with inherited or congenital cardiomyopathy have a greater chance of survival into adulthood. Women with ICDs in this group are now more likely to reach reproductive age. However, pregnancy represents a challenge for clinicians, as no guidelines for the treatment of pregnant women with an ICD are currently available. Methods: To analyze this issue, we performed a systematic screening of the litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In addition, the influence of WCD shocks on the fetal outcome is unclear. In contrast, effectiveness and safety of ICD shocks in pregnancy were already shown in several studies [34] , [35] , [36] . These reports, found no increased risk for adverse fetal outcomes following the occurrence of ICD shocks [35] , [36] , [37] , [38] , [39] , [40] .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the influence of WCD shocks on the fetal outcome is unclear. In contrast, effectiveness and safety of ICD shocks in pregnancy were already shown in several studies [34] , [35] , [36] . These reports, found no increased risk for adverse fetal outcomes following the occurrence of ICD shocks [35] , [36] , [37] , [38] , [39] , [40] .…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, effectiveness and safety of ICD shocks in pregnancy were already shown in several studies [34] , [35] , [36] . These reports, found no increased risk for adverse fetal outcomes following the occurrence of ICD shocks [35] , [36] , [37] , [38] , [39] , [40] . Similar results can be expected for WCD shocks, but further studies are necessary.…”
Section: Discussionmentioning
confidence: 92%
“…Literature on pregnant women with an ICD in situ is limited. To date, four retrospective studies on this subject have been published, with a total of 76 included patients with an abdominal or TV‐ICD, 10,15–17 as well as one meta‐analysis 18 . In these studies, no inappropriate ICD shocks by these types of ICD were reported.…”
Section: Discussionmentioning
confidence: 99%